2020
DOI: 10.1038/s41598-020-71242-0
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface sensing difference in waveforms at the same frequency with reduced power level

Abstract: We numerically demonstrate a new type of waveform-selective metasurface that senses the difference in incoming waveforms or pulse widths at the same frequency. Importantly, the proposed structure contains precise rectifier circuits that, compared to ordinary schottky diodes used within old types of structures, rectify induced electric charges at a markedly reduced input power level depending on several design parameters but mostly on the gain of operational amplifiers. As a result, a waveform-selective absorbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Finally, it is worth mentioning that, being these devices equipped with non-linear diode, they are inherently powerdependent devices and their time-dependent filtering functionalities could be disabled, particularly if receiving too low powered signal. Indeed, it has been demonstrated that more complex circuit solutions relying on the use of operational amplifiers can dramatically mitigate this issue [71].…”
Section: Waveform-selective Filtering Modules For Antennasmentioning
confidence: 99%
“…Finally, it is worth mentioning that, being these devices equipped with non-linear diode, they are inherently powerdependent devices and their time-dependent filtering functionalities could be disabled, particularly if receiving too low powered signal. Indeed, it has been demonstrated that more complex circuit solutions relying on the use of operational amplifiers can dramatically mitigate this issue [71].…”
Section: Waveform-selective Filtering Modules For Antennasmentioning
confidence: 99%
“…[29] Additionally, Tanikawa et al introduced nonlinear circuit-based MSAs composed of Schottky diodes and other lumped elements, which were capable of distinguishing short pulses and continuous waves (CWs) at the same frequency. [30] Such nonlinear circuit-based MSAs hold promise for distinguishing signals with different waveforms (more specifically, pulse widths) and powers at the same frequency in wireless communication, effectively addressing the EM interference and compatibility issues in accordance with different waveforms. [31][32][33][34][35][36] For instance, MSAs were integrated with antenna design to receive particular pulsed signals while reducing interference from other signals at the same frequency.…”
Section: Introductionmentioning
confidence: 99%
“…[44] Since then, this waveform-selective concept has provided an additional degree of freedom in modulating the absorption behavior of incident EM wave signals at the same frequency depending on the waveform, notably the pulse width. [45][46][47][48][49][50][51][52] However, until now, all these waveform-selective MSAs operated only in the microwave or even radio-frequency region due to the limitation of the operation frequency of the nonlinear circuit components (such as rectifier diodes) in practice.…”
Section: Introductionmentioning
confidence: 99%